Psychiatric morbidity among school students - Nayak, Madhu; Lavania, Sagar (International Journal of Contemporary Pediatrics, 2018)
Background: Psychiatric morbidity represents most important problem among all children including school going children worldwide, prevalence of psychiatric disorders among children has been reported to be 14-20% across various studies Child and adolescent population are susceptible for psychiatric morbidity; we plan to evaluate the prevalence of psychiatric morbidity among school going students of class 8 and 9. Methods: It was a cross sectional observational study. Study was conducted in two steps, firstly screening was done with GHQ-12 along with socio-demographic data sheets, on second step students scoring above GHQ cutoff score were interviewed by consultant psychiatrist and diagnosis was made as per ICD 10 DCR. Results: A total of 128 students, consisting of 73 male and 55 females (57% and 43% respectively) with mean age of 13.02±0.58 years participated. With GHQ screening 38 students scored above the cut-off marks and finally 6 children were diagnosed as generalized anxiety disorder, 6 as Depression, 1 as elimination disorder (nocturnal enuresis), 3 as separation anxiety, 4 cases of OCD, and 2 cases of Panic disorder totaling to 21 (16.41%) students. Conclusions: This study finds a prevalence of 16.41% of the psychiatric morbidity among school students.